Structural and functional imaging of large and opaque plant specimens. (24th April 2019) - Hesse, Linnea; Bunk, Katharina; Leupold, Jochen; Speck, Thomas; Masselter, Tom
Abstract: Three- and four-dimensional imaging techniques are a prerequisite for spatially resolving the form–structure–function relationships in plants. However, choosing the right imaging method is a difficult and time-consuming process as the imaging principles, advantages and limitations, as well as the appropriate fields of application first need to be compared. The present study aims to provide an overview of three imaging methods that allow for imaging opaque, large and thick (>5 mm, up to several centimeters), hierarchically organized plant samples that can have complex geometries. We compare light microscopy of serial thin sections followed by 3D reconstruction (LMTS3D) as an optical imaging technique, micro-computed tomography (µ-CT) based on ionizing radiation, and magnetic resonance imaging (MRI) which uses the natural magnetic properties of a sample for image acquisition. We discuss the most important imaging principles, advantages, and limitations, and suggest fields of application for each imaging technique (LMTS, µ-CT, and MRI) with regard to static (at a given time; 3D) and dynamic (at different time points; quasi 4D) structural and functional plant imaging. Abstract : Three imaging techniques for structural and functional plant imaging of opaque, large (>5 mm, up to several centimeters), hierarchically organized plant samples are compared.